Arterial Stiffness in Nonhypertensive Type 2 Diabetes Patients in Ghana - Kwame Yeboah; Daniel A. Antwi; Ben Gyan (International Journal of Endocrinology)
Background. Increased arterial stiffness is an independent cardiovascular risk factor in diabetes patients and general population. However, the contribution of diabetes to arterial stiffness is often masked by coexistent obesity and hypertension. In this study, we assessed arterial stiffness in nonhypertensive, nonobese type 2 diabetes (T2DM) patients in Ghana. Methods. In case-control design, 166 nonhypertensive, nonobese participants, comprising 96 T2DM patients and 70 nondiabetes controls, were recruited. Peripheral and central blood pressure (BP) indices were measured, and arterial stiffness was assessed as aortic pulse wave velocity (PWVao), augmentation index (AIx), cardioankle vascular index (CAVI), and heart-ankle pulse wave velocity (haPWV). Results. With similar peripheral and central BP indices, T2DM patients had higher PWVao (8.3 ± 1 versus 7.8 ± 1.3, p=0.044) and CAVI (7.9 ± 1.2 versus 6.9 ± 0.7, p=0.021) than nondiabetic control. AIx and haPWV were similar between T2DM and nondiabetic controls. Multiple regression models showed that, in the entire study participants, the major determinants of PWVao were diabetes status, age, gender, systolic BP, and previous smoking status (β = 0.22, 0.36, 0.48, 0.21, and 0.25, resp.; all p<0.05); the determinants of CAVI were diabetes status, age, BMI, heart rate, HbA1c, total cholesterol, HDL cholesterol, and previous smoking status (β = 0.21, 0.38, 0.2, 0.18, 0.24. 0.2, −0.19, and 0.2, resp.; all p<0.05). Conclusion. Our findings suggest that nonhypertensive, nonobese T2DM patients have increased arterial stiffness without appreciable increase in peripheral and central pressure indices.